Desarrollo de un sitio web que permita mejorar el proceso de enseñanza aprendizaje del idioma inglés en los estudiantes de octavo a décimo año de la escuela de educación general básica “Emilio Arévalo” ubicada en la comunidad Morasloma, cantón Oña, provincia del Azuay - Barreto Aguilar, Alex Manuel (2015)
The research focuses on improving the process of learning the English language students from Eighth to Tenth year of the School of General Education Basic "Emilio Arevalo", so to achieve this goal is proposed to develop a website that contains tools and information necessary for students seeking this objective reality is worked with students from Eighth to Tenth year of general basic education to meet your needs and difficulties presented. The website seeking to improve the student's actual teaching process as this became a tool free and easy access to information necessary and appropriate to support their study of English and replacement of traditional consultations on physical media. Also to be linked to a virtual platform allowed the student to interact with their teacher, request information, participate in forums, take tests, visualize your progress in the course, etc. Thus to have a stronger link with the student and the subject was able to increase the student's attention to the subject of English and thus managed to soak students basic and elementary knowledge possessed by the English language. And improved the process of learning as well as physics class when the class virtually be supported so better learning in the student was achieved and also a modern virtual tool for both the teacher and the institution was obtained.